If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7(2x + 8) = 14 Reorder the terms: -7(8 + 2x) = 14 (8 * -7 + 2x * -7) = 14 (-56 + -14x) = 14 Solving -56 + -14x = 14 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '56' to each side of the equation. -56 + 56 + -14x = 14 + 56 Combine like terms: -56 + 56 = 0 0 + -14x = 14 + 56 -14x = 14 + 56 Combine like terms: 14 + 56 = 70 -14x = 70 Divide each side by '-14'. x = -5 Simplifying x = -5
| 8z+22=3(3z+11)z | | 11x-3x=400 | | (x^4)-(5x^2)+(4)=0 | | 6(2/3x-7/6)=6*7/2 | | -2y-1=4x+3 | | b+9=24 | | 23x=173 | | 4(x+19)=3x+41 | | y=-4y+1 | | 2(-.26)+7.5=6.2-3(-.26) | | 13x+21=47 | | 3a+7b=1650 | | f(t)=2.25+0.75x | | 4+x=4x-23 | | 0.2c-0.6+.5c=5 | | 3(6+8)=24+18x | | 10m^2-6=404 | | -11.1-2.2x=2.2x/7.7-2x-x^2 | | x^3+5x^2-5x-25=0 | | 1x-2=6x+5 | | (3a+19)+2z= | | 5w+2=w+10 | | x-200=.2x | | x(x+8)(x+7)=0 | | 2r+3u=2(3r+6) | | -2(x+5)=4-(-5) | | 4x-20=3x+15 | | 3x^2+8x=8x^2-16x | | 5w-8=w+10 | | -1/5(x+3)=-13 | | 4n^2-9=-46 | | 6x-7x=-4 |